KAJIAN EMPIRIS PROGRAM DESA TANGGUH BENCANA (DESTANA) TERHADAP KETANGGUHAN MASYARAKAT PESISIR DALAM MENGHADAPI BENCANA TSUNAMI: STUDI KASUS DI DUA GAMPONG PESISIR KABUPATEN ACEH BESAR - Saroji .; Saiful Mahdi; Eka Sri Mulyani (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Coastal area is the most tsunami prone area. Many efforts have been done either by government or non-government organizations to minimize disaster impact. Resilient village program (Destana Program) is one of those efforts that is aimed to obtain community resilience in facing disasters. The purpose of this research is to examine Destana Program that had been done by two different organizations toward community resilience in coastal area after tsunami: study case of two villages in Aceh Besar. The data within this research were collected by delivering questionnaires, interviews and direct observation in relation to community resilience. The collected data were tested by using independent sample t-test and categorized based on the average. The results show that is differences between Destana Program which is conducted by Local Management Agency of Aceh Besar and by non-government organization. The results also indicate that resilience score of Gampong Kahju is higher than Gampong Pulot and the score of trained people is higher than untrained people. Resilience level of these two villages after Destana Program was conducted is in Destana Madya, it means that the resilience of these two coastal villages is in moderate level in facing tsunami.